Fatal Incidents in Australia's Older Farmers (2001–2015). Issue 2 (3rd April 2017) - Monaghan, Noeline; Lower, Tony; Rolfe, Margaret
ABSTRACT: Objectives: This study assesses nonintentional injury deaths of older farmers and the causal agents associated with these fatalities in Australia (2001–2015). It also explores approaches based on the hierarchy of risk controls to reduce fatalities and injuries in this cohort. Methods: Data on farm-related incidents were sourced from the National Coroners Information System (NCIS) for the study period and coded. Rates were calculated and regression analyses completed to assess trends over time. Results: Those in the 50+ years category ( n = 610) accounted for 49.8% of all on-farm nonintentional injury deaths, with males ( n = 566) dominating the cases. The annual mean was 40.66 cases ( SD = 8.08) and the average rate 36/100, 000. Trend analysis revealed a nonstatistically significant ( P < 0.05) increase in cases over the period. Farm vehicles and machinery were responsible for almost two thirds of the fatal cases. Conclusion: Nonintentional fatality rates for older farmers have remained relatively unchanged for a significant period in Australia. There is a need to examine additional approaches that not only maintain the benefits of work activity for older farmers but also balance this against a safety perspective.